(untitled) (Research, Society and Development, 2022)
Introduction: the human body requires nutritional and caloric needs to maintain the supply of energy and nutrients to the tissues and thus, physiological functioning. Furthermore, during childhood, adequate nutrition is essential to ensure neurodevelopment, a functioning immune system, and quality of life. In a hospitalized situation, is known that patients are at risk of nutritional deterioration, adversely affecting clinical outcomes. Objectives: to assess the nutritional status and establish a relationship with the length of stay of children hospitalized in a pediatric ward of a philanthropic hospital in the city of Aracaju. Methodology: this is an observational, prospective and analytical study involving children older than 29 days and younger than 9 years in a pediatric ward, evaluated and classified by nutritional status through body mass index/age Z-score curves (Z BMI), Z-score for height/age (Z H/A), Z-score for weight/height (Z W/H) and Z-score for weight/age (Z W/A). Results: the sample consisted of 235 patients, 52.8% of whom were male. The prevalent age range was 29 days to 2 years (81.3%), the most frequent clinical diagnosis was pneumonia (23.8%). Malnutrition at the time of hospital admission was observed in 51.9% of patients. Conclusion: hospitalized children have a double burden of malnutrition, coexisting deficit and excess weight that can compromise the outcome of hospitalization.